Correlates of burden among caregivers of the mentally ill in Eastern Visayas - Ganzo, Amabel A.
The deinstitutionalization of mental health services has recognized the caregivers of the mentally ill at home as important workforce in health care. Studies that looked into how burdened these caregivers are, and what the factors associated with their burden are, have been done in other countries, but none have been done in other countries, but none have been done locally.{{{{This study had the objective of determining the extent of burden of the caregivers of the mentally ill in Eastern Visayas, and correlating it with identified characteristics of the caregiver, the patient, and their environment. It aimed at pinpointing caregivers at risk so an intervention program to assist them can be made.{{{{Sixty-seven caregivers, who understood the waray-waray dialect, and were willing to participate through an informed consent, were interviewed using the wara-waray versions of the Burden Factors Interview Form and the Zarit Burden Interview.{{{{The results showed that most of the caregivers were aged 61 and above with a mean age of 49.9 (sd=15.45). Most of them (68.7%) were fenales, married (56.7%), had a mean monthly income of P4,914.43 (sd=P7,567.79), and parents of the mentally ill (52.2%), with duration of caregiving of 5 years or more (70%).{{{{Extent of burden was moderate (x=55.5; sd=14.48), as measured by the Zarit Burden Interiew.{{{{Negative correlation at ...